2004
DOI: 10.1123/jsep.26.4.616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Same-Sex and Mixed-Sex Exercise Settings on the Social Physique Anxiety and Exercise Intentions of Males and Females

Abstract: Situational social physique anxiety (SPA) and immediate exercise intentions in male and female fitness club members were examined in response to all-female, all-male, and mixed-sex exercise setting scenarios. Overall, women showed higher levels of situational SPA than men. SPA increased significantly from an all-female, to a mixed-sex, to an all-male exercise setting for women but not for men. More women indicated they would shorten their workout in response to the all-male vs. all-female or mixed-sex exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 11 publications
3
47
2
1
Order By: Relevance
“…Boys were coded as value 1, and girls were coded as value 2. Gender and BMI were introduced to control for their effects, as the literature has shown a relationship between these variables and social physique anxiety (Eklund et al, 1997;Hagger et al, 2010;Hausenblas & Fallon, 2002;Kruisselbrink et al, 2004;Thompson & Chad, 2000). Following the sequence proposed by SDT (basic psychological needs → types of motivation → consequences), we entered the needs for autonomy, competence and relatedness in…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boys were coded as value 1, and girls were coded as value 2. Gender and BMI were introduced to control for their effects, as the literature has shown a relationship between these variables and social physique anxiety (Eklund et al, 1997;Hagger et al, 2010;Hausenblas & Fallon, 2002;Kruisselbrink et al, 2004;Thompson & Chad, 2000). Following the sequence proposed by SDT (basic psychological needs → types of motivation → consequences), we entered the needs for autonomy, competence and relatedness in…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we studied how motivation mediates the relationship between the basic psychological needs and social physique anxiety. In the analysis, we controlled for the influence of gender and body mass index (BMI), as prior research has shown that girls tend to display higher levels of social physique anxiety (Eklund, Kelley, & Wilson, 1997;Hagger et al, 2010;Kruisselbrink, Dodge, Swanburg, & MacLeod, 2004;Mülazimoğlu-Balli, Koca, & Aşçi, 2010), and other studies have shown that BMI is positively related to social physique anxiety (Hausenblas & Fallon, 2002;Thompson & Chad, 2000).…”
Section: Objectives and Hypotheses Of This Studymentioning
confidence: 99%
“…For example, in a 4-year longitudinal study among Hispanic adolescents, body dissatisfaction was a significant predictor of depressive symptoms for both the girls and boys (Ferreiro et al, 2012). Furthermore, research has demonstrated that negative body evaluations can be detrimental to both boys and girls, particularly during adolescence (Cohane & Pope, 2001;Davison & McCabe, 2006;Erikson, 1968;Kruisselbrink et al 2004). Body satisfaction has been conceptualized as a structural component of the self (Guerin, Marsh, & Famose, 2004;Marsh, Martin, & Jackson, 2010), and is thought to contribute to overall feelings of general worth.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to gender, women have reported that they would experience higher levels of SPA when working out in all-male and mixed-sex settings than they would in all-female settings whereas males reported lower levels of SPA regardless of the gender of other exercisers in the settings (Kruisselbrink et al, 2004). Interestingly, the women in the Kruisselbrink et al study reported they would shorten their exercise session in all-male settings relative to their intentions in all-female or mixed-sex exercise scenarios.…”
Section: Self-presentational Responses On the Exercise Environmentmentioning
confidence: 99%
“…Environmental attributes including exercise setting itself (Bain, Wilson, & Chaikind, 1989;Van Raalte, Cunningham, Cornelius, & Brewer, 2004), norms on attire, fitness leader characteristics and leadership style (Raedeke, Focht, & Scales, 2007), social composition of participants, and gender make-up of the exercise group (Kruisselbrink, Dodge, Swanburg, & MacLeod, 2004), can potentially influence psychological responses to acute bouts of exercise.…”
Section: Self-presentational Responses On the Exercise Environmentmentioning
confidence: 99%